Biologically-inspired computing for the arts scientific data through graphics - Ursyn, Anna, 1955- (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2012)
"Images support connections between biology, engineering, and material sciences resulting in a growing partnership among academia, laboratories, and industry. Scientists focus on biology-inspired research to understand how biological systems work, and then create systems and materials that would have efficiency and precision of living structures. The Art-Science connection has become one of prominent trends exemplified by themes presented in journals, conferences, and books. Biologically-Inspired Computing for the Arts: Scientific Data through Graphics comprises a collection of authors' individual approaches to the relationship between nature, science, and art created with the use of computers. Themes discussed in the book relate to the use of visual language in communication about biologically-inspired scientific data, visual literacy in science, and application of practitioner's approach. This comprehensive reference will assist programmers, scientists, engineers, computer science and science-oriented students in creating and effectively communicating their projects using science-related knowledge"--Provided by publisher.